Does Green Marketing Will Be Impact to The Purchase Decision? A Theoretical Perspective - Arief, Mohammad; Kurriwati, Nirma (Archives of Business Research, 2017)
At present, the green marketing concept has been developed. Some perspectives from this concept has been studied and used by researchers to do that work. The results of the study causes various approaches can be used of this concept. Some previous study resulted that green marketing will encourage someone to take purchasing decisions. This article aims to exploration the green marketing concept through behavioral approach, particularly in the process of purchase decision-making. The development of the green marketing concept and some of the purchase decision has been made also be discussed.